In-situ observation of the phase evolution during an electromagnetic-assisted sintering experiment of an intermetallic γ-TiAl based alloy. (1st January 2022) - Musi, Michael; Galy, Benjamin; Monchoux, Jean-Philippe; Couret, Alain; Clemens, Helmut; Mayer, Svea
Abstract: Electromagnetic-assisted sintering offers the possibility for a time-efficient densification of intermetallic γ-TiAl based powders. Since the microstructure of the densified material and, thus, its mechanical properties can be controlled by the imposed temperature profile, the kinetics and transformations of the occurring phases are of particular interest. The present study describes a diffraction setup for the in-situ observation of the phase evolution by high-energy X-ray diffraction during an electromagnetic-assisted sintering process using induction heating. Starting from Ti-46.3Al-2.2W-0.2B powder (in at.%), this experiment grants time-resolved insights into the non-equilibrium and equilibrium phase transformations during this powder consolidation process for the first time. The microstructural accordance of the electromagnetic-assisted sintered specimen with spark plasma sintered material densified at the same dwell temperature highlights the transferability of both techniques and allows an allocation of the determined phase transformation data to the spark plasma sintering technology. Graphical abstract: Image, graphical abstract